Influence of Protonic Ionic Liquid on the Dispersion of Carbon Nanotube in PLA/EVA Blends and Blend Compatibilization - Lopes Pereira, Elaine Cristina; da Silva, Maria Eduarda C. Fernandes; Pontes, Ketly; Soares, Bluma Guenther (Frontiers in Materials, 2019)
In this work, immiscible poly(lactic acid) (PLA)/poly(ethylene vinyl acetate) (EVA) composites with 1 phr of multi‐walled carbon nanotube (CNT) and different concentration of protonic – based imidazolium ionic liquid (mimbSO3H.Cl) were prepared. The protonic ionic liquid (IL) was able to act as dispersing agent for CNT and as compatibilizing agent for the PLA/EVA blend. The multicomponent nanocomposites from the mixture of PLA and EVA containing CNT functionalized with ionic liquid, IL (CNT/ILSO3H) were characterized by mechanical and dynamic - mechanical (DMA) tests, electrical conductivity analyses, differential scanning calorimetry (DSC), X-ray diffraction analysis and rheological measurements, as well as chromatographic gel permeation (GPC), and scanning electron microscopy (SEM). The non covalent functionalization CNT resulted in composites with outstanding electrical and dielectric properties. The high dispersion of CNT promoted by the IL resulted in the formation of a physical networked structure, which was responsible for the higher electrical conductivity and higher melt viscosity. The crystallization process of PLA phase was improved with the presence of CNT/ILSO3H. The degradation process during the transesterification reaction did not significantly affect the mechanical properties. The present work highlights the dual role of the IL as compatibilizing and dispersing agent and opens new perspectives for developing new conducting systems with low percolation threshold based on the good dispersion of CNT and the confinement of the filler within a phase of a multiphasic polymeric system.